The effects of crop rotation combinations on the soil quality of old apple orchard - Haiyan Wang; Yuefan Sheng; Weitao Jiang; Fengbing Pan; Mei Wang; Xuesen Chen; Xiang Shen; Chengmiao Yin; Zhiquan Mao (Horticultural Plant Journal, 2022)
This study investigated the effects of six crop rotation combinations on the soil quality of old apple orchard and seedling growth of Malus hupehensis Rehd. (apple rootstock) under pot conditions. The inhibitory effects of crops such as Allium fistulosum, Brassica juncea, and Triticum aestivum on four species of Fusarium were observed and compared in six treatments. These were continuous cropping (CK), fumigation with the methyl bromide (FM), rotating A. fistulosum only (R1), rotating A. fistulosum and T. aestivum (R2), rotating A. fistulosum, B. juncea, and T. aestivum (R3), and fallow (FC) in a year. The results showed that the biomass of Malus hupehensis Rehd. seedlings increased significantly. The root length increased and the root architecture was optimized. The respiration rate of the root system was increased by about 1 time after rotation. The treatments of R1, R2, R3, and FC increased bacterial count by 232.17%, 96.04%, 316.21%, and 60.02%, respectively. However, the fungi were reduced in varying degrees and bacteria/fungi ratio was increased by 5–10 times. The enzyme activities, pH, and organic matter were increased, but soil bulk density was decreased. Phenolic acids such as phloridzin was decreased significantly. The copy number of four Fusarium species declined by 85.59%, 74.94%, 69.68%, and 54.41% after rotating three different crops (R3 treatment). The root volatiles of three plants inhibited mycelial growth and spore germination of four Fusarium species.